Advances in the diagnosis and treatment of Hodgkin lymphoma and systemic anaplastic large cell lymphoma. (September 2015) - Hutchings, Martin; Piris, Miguel A.; Baiocchi, Otavio; Hertzberg, Mark
Abstract: Current management of Hodgkin lymphoma (HL) allows high cure rates to be achieved with initial therapy in both early-stage and advanced-stage disease. However, adverse events and the emergence of late effects are important issues for patients who respond well to frontline treatment. A further challenge in HL is the treatment of patients who are either refractory to, or relapse following, initial therapy. High-dose chemotherapy with autologous stem cell transplantation (HDCT/ASCT) is a potentially curative second-line treatment option for many patients with relapsed/refractory (R/R) HL. However, not all patients are candidates for HDCT/ASCT, and the frequency and duration of responses vary. For patients who fail HDCT/ASCT, current treatment options include further salvage chemotherapy, allogeneic transplantation or novel targeted therapies. Similar issues surround the management of R/R systemic anaplastic large cell lymphoma (sALCL), which is a rare and aggressive tumour. CD30 is strongly expressed in both HL and sALCL tumour cells and is a promising therapeutic target, as demonstrated by the activity of the novel antibody–drug conjugate brentuximab vedotin. New approaches to individualising and optimising patient management, including improved application of imaging, better prognostication through use of biomarkers and the potential use of new treatment combinations and agents targeting signalling pathways in malignant cells, may help to improve outcomes. The case studies included herein were presented at a symposium during the European Hematology Association (EHA) meeting in 2014. This publication aims to share clinical experiences and solutions to the management of HL and sALCL patients in very challenging disease settings.